AMINO ACID ACCUMULATION IN ETHIONINE-RESISTANT SACCHAROMYCES CEREVISIAE - Sorsoli, W. A. (1964)
Sorsoli, W. A. (Oregon State University, Corvallis), K. D. Spence, and L. W. Parks. Amino acid accumulation in ethionine-resistant Saccharomyces cerevisiae. J. Bacteriol. 88:20–24. 1964.—Recessive ethionine-resistant strains of Saccharomyces cerevisiae possess a genetic lesion affecting the concentration of amino acids nonspecifically in the expandable pool of the organism. This area, which may be linked to a methionine gene, is highly mutable and accounts for resistance to certain amino acid analogues. Other mutations result in ethionine resistance by a mechanism unrelated to the amino acid uptake system.